Swimming Pools Causing Electromagnetic Interference on Cardiac Devices: A Case Series - Lisa M. Conte; Adam J. Kisling; Matthew Needleman (Annals of Internal Medicine: Clinical Cases)
Electromagnetic interference (EMI), also called radiofrequency interference, is unwanted electromagnetic signals from extracardiac sources that are detected by cardiac pacemakers or defibrillators, potentially affecting device therapies. After device implantation, patients are educated about the risks for EMI from sources like cell phones or laptops, but swimming pools often are not included in this discussion. We report 2 cases of EMI from swimming pools that resulted in inappropriate device therapies. Although no catastrophic events occurred in these cases, EMI has the potential to cause changes in device therapy that may lead to devastating clinical outcomes.